Comparative Study of the Antioxidant Power of Polyphenols of Leaves, Fruits, and Bark of Pistacia atlantica Desf. from Morocco. (20th May 2022) - Zerkani, H.; Tagnaout, I.; Khiya, Z.; Boutahiri, S.; Amalich, S.; Fadili, K.; Cherrat, A.; Mouradi, A.; Benhlima, N.; Zair, T.
Abstract : Pistacia atlantica Desf. is a widely used plant species in the traditional medicine for its various pharmacological properties. The aim of this study is the valorisation of polyphenols and the antioxidant power of three organs from Pistacia atlantica Desf. (leaves, fruits, and bark). Phytochemical screening of secondary metabolites was performed using precipitation and coloring reactions. Total phenols, flavonoids, and condensed tannins were quantified, respectively, by the Folin-Ciocalteu method, the aluminum trichloride method, and the vanillin method. Evaluation of the antioxidant activity was made using two methods: DPPH∗ (2, 2 ′ -diphenyl-1-picryl hydrazyl) and FRAP (ferric reducing antioxidant power). The obtained results showed that the three organs of Pistacia atlantica are rich in total phenols, flavonoids, and condensed tannins. The highest contents of total phenols and flavonoids are recorded by the crude fruit extract, 723 mg EGA/gE and 34.57 mg EQ/gE, respectively, while the highest content of condensed tannins is recorded in the butanolic extract of the leaves (997.58 mg ECat/gE). The antioxidant activity of the three organs extracts from Pistacia atlantica Desf. confirmed their strong antiradical power, much higher than that of ascorbic acid and BHA (butylated hydroxyanisole). Indeed, the concentration of the crude extract of P. atlantica leaves reducing 50% of the DPPH∗ free radicals (IC50 ) is 27.22 μ g/ml. This concentration is much lower than those of ascorbic acid (31.44 μ g/ml) and BHA (46.25 μ g/ml). The antioxidant power using the FRAP method has also shown that the leaves extract of this species has a much higher reducing capacity of iron than those of the reference standards. A positive correlation between antioxidant capacities and flavonoids contents of leaves and fruits extracts was observed. The two methods (DPPH∗ and FRAP) proved that the three organ extracts of Pistacia atlantica possess very remarkable antioxydant activity. These extracts could be exploited as natural antioxidants against the oxidation phenomenons and the oxidative stress in several fields (food, cosmetic, pharmaceutic, and others).